Beyond the Classroom: Investigating the Relationship between Psychomotor Development and Academic Achievement in 4-12-Year-Olds - Nídia Amorim; Adilson Marques; Sofia Santos (MDPI AG, 2024)
Background/Objectives: The relevance of psychomotor skills in children's growth is being increasingly recognized. The transversal role of psychomotor skills in learning performance is described through a link between cognitive and motor functioning, promoting socio-affective-expressive competencies, but there is a scarcity of evidence from the field. A two-fold goal was defined: to investigate the relationship between psychomotor functions and academic performance and to examine the factors affecting children's academic performance. Methods: The Portuguese versions of the Neuropsychomotor Functions Assessment Battery for Children (NPmot.pt), Preschool Diagnostic Tasks (PRE), and School Learning Skills Battery (SLSB) were applied to 350 children (85.72 ± 24.23 months) with and without disabilities attending mainstream schools. Results: Pearson correlations and regression analyses were used. NPmot.pt domains showed moderate to strong correlations with PRE domains (0.30 < r < 0.82) and weak ones with SLSB domains (r < 0.30). Psychomotor development is a stronger predictor (p < 0.001) of pre-academic performance outcomes: (βTonus = 0.67, βGross Motor Skills = 1.04, βSpatial Orientation = −1.44, βRhythm = −1.59 and βAuditory Attention = 3.68) than of academic performance above 7 years old (p > 0.05). Conclusions: Results strengthen the importance of psychomotor skills development from an early age, also at school, with implications for an early psychomotor assessment and intervention for children with and without disabilities. Tailor-fit interventions, including strategies to improve psychomotor skills, should be promoted during the school process of all children for a successful learning process.